2018
DOI: 10.1371/journal.pone.0192251
|View full text |Cite
|
Sign up to set email alerts
|

Does poor oral health status increase the risk of falls?: The JAGES Project Longitudinal Study

Abstract: We sought to examine if self-reported oral health conditions regarding difficulty eating tough foods, dry mouth, choking, number of teeth and denture use are associated with incident falls. Our study was based on panel data from the Japan Gerontological Evaluation Study conducted in 2010 and 2013 using self-administered questionnaires. Data from 19,995 male and 20,858 female community-dwelling older people aged ≥65 years without a history of falls within the previous year in 2010 were analyzed. Multilevel logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Physical health and postural stability have been linked to poor oral health conditions in 21 articles. 17 , 72 , 73 , 100 - 117 The majority of these were prospective cohort studies conducted in Japan (n = 12). Avlund et al reported that Danish elderly aged ⩾ 70 years with a fewer number of teeth (1-9 teeth) had almost twice (adjusted OR = 1.91, 95% CI: 0.79-4.62) the odds of fatigue as those having ⩾ 20 teeth over 10 years after adjusting for confounding variables such as smoking status and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical health and postural stability have been linked to poor oral health conditions in 21 articles. 17 , 72 , 73 , 100 - 117 The majority of these were prospective cohort studies conducted in Japan (n = 12). Avlund et al reported that Danish elderly aged ⩾ 70 years with a fewer number of teeth (1-9 teeth) had almost twice (adjusted OR = 1.91, 95% CI: 0.79-4.62) the odds of fatigue as those having ⩾ 20 teeth over 10 years after adjusting for confounding variables such as smoking status and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
“… 103 , 116 Two studies by Mochida et al and Yamamoto et al reported that poor self-reported oral health conditions, number of teeth and chewing disability were significantly ( P -values < .05) associated with incident falls in Japanese older adults where findings from 1 study reported that the odds of incident falls among Japanese elderly aged ⩾ 65 years having 19 or fewer teeth were 2.5 (OR = 2.50, 95% CI: 1.21-5.17) times greater than those having ⩾ 20 teeth over a 3-year follow-up period, after adjusting for confounding variables such as sex, functional disability during follow-up period, depression, self-rated health and education. 106 , 111 Poor oral health status has also been associated with increased risk of functional and physical disability in eleven studies. 17 , 72 , 73 , 100 - 102 , 104 , 107 , 109 , 113 , 114 A recent study by Ramsay et al reported that edentulous elderly aged between 71 and 92 years were associated with a 2-fold (OR = 1.90, 95%CI = 1.03-3.52) increase in the risk of incident frailty compared to those having teeth over 3 years after adjusting for confounding variables such as smoking status, social class, history of cardiovascular disease or diabetes mellitus, and medications related to dry mouth.…”
Section: Resultsmentioning
confidence: 99%
“…There is still much to find out about dry mouth and its associations (41). Despite diverse approaches to the condition's measurement, just over one in four people in adult age or older suffer from xerostomia, with higher rates observed among elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters used as covariates that may correlate with falls were selected based on previous studies [ 7 , 17 , 21 , 22 , 23 , 24 ]. These were age, sex, educational attainment, annual-equivalent income, physical ability, instrumental activities of daily of living (IADLs), self-recognition of forgetfulness, current medical conditions related to falls, and number of medications taken.…”
Section: Methodsmentioning
confidence: 99%